2014
DOI: 10.3109/0886022x.2014.976131
|View full text |Cite
|
Sign up to set email alerts
|

The optimal timing of hemoperfusion component in combined hemodialysis–hemoperfusion treatment for uremic toxins removal

Abstract: The combination of hemodialysis-hemoperfusion (HDHP) has been proved to be superior to hemodialysis (HD) in eliminating uremic toxins. There are two methods of combination of HD and HP: the HP regime is utilized during the first two-hour an early HP conducted HDHP (EHDHP) or the last two-hour late HP conducted HDHP (LHDHP) of 4 h regular HD session. The present study was to compare these two methods in uremic toxins removal. Twenty adult chronic HD patients were enrolled in this self-control method study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In this study, the levels of serum clinically related indicators and inflammatory factors in uremic patients before and after treatment were detected, and it was found that the β2-MG, Cr, BUN, PTH, CRP, and IL-6 levels after treatment were significantly lower than those prior to treatment. This showed that hemodialysis combined with hemoperfusion could effectively remove toxins and improve the inflammatory state of uremic patients, which was consistent with the results of previous studies (6,31,36); hemodialysis combined with hemoperfusion had a high value in treating uremia. The Pearson correlation coefficient analysis revealed that before treatment, serum miR-155 level was significantly positively correlated with clinically related indicators of β2-MG, Cr, BUN, and PTH (P<0.001), and it was significantly positively correlated with levels of CRP and IL-6 inflammatory factors (P<0.001).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the levels of serum clinically related indicators and inflammatory factors in uremic patients before and after treatment were detected, and it was found that the β2-MG, Cr, BUN, PTH, CRP, and IL-6 levels after treatment were significantly lower than those prior to treatment. This showed that hemodialysis combined with hemoperfusion could effectively remove toxins and improve the inflammatory state of uremic patients, which was consistent with the results of previous studies (6,31,36); hemodialysis combined with hemoperfusion had a high value in treating uremia. The Pearson correlation coefficient analysis revealed that before treatment, serum miR-155 level was significantly positively correlated with clinically related indicators of β2-MG, Cr, BUN, and PTH (P<0.001), and it was significantly positively correlated with levels of CRP and IL-6 inflammatory factors (P<0.001).…”
Section: Discussionsupporting
confidence: 92%
“…If treatment is not timely, uremia caused by renal failure may aggravate the disease and eventually lead to death (3,4). At present, findings have shown that hemodialysis combined with hemoperfusion has a good effect on the treatment of uremia (5,6). Hemodialysis can remove blood urea nitrogen (BUN), creatinine (Cr) and bilirubin.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that HD + HP treatment was better than HD treatment in the clearance of iPTH, β2-MG, and CysC. This is consistent with results of earlier literatures [16,25,27]. HP used the adsorption of activated carbon in the perfusion apparatus to remove iPTH, β2-MG, and CysC, and the combination of HP and HD can make up for the deficiency in removing macromolecular substances in HD alone.…”
Section: Discussionsupporting
confidence: 81%
“…HP used the adsorption of activated carbon in the perfusion apparatus to remove iPTH, β2-MG, and CysC, and the combination of HP and HD can make up for the deficiency in removing macromolecular substances in HD alone. Furthermore, this study revealed that moderate-and macro-molecular-weight toxins β2-MG and CysC could not be removed by HD treatment alone [16], and the concentrations of these 2 toxins in the HD group were higher after dialysis than before dialysis. The reason may be that ultrafiltration during HD caused loss of water, reduced blood volume, and concentrated blood, resulting in an increase in the concentrations of components that had not been removed in the process [28].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation